The Experiment of Recycled Paper Making Process and Its Water Resistance on a Household Scale Industrial. - Suryandono, Alexander Rani; Hardiansyah, Wisnu Agung; Lazulfa, Nada Indana; Nabilah, Asti Ainun (Department of Architecture and Planning, Faculty of Engineering, Universitas Gadjah Mada, 2024)
White paper waste usually is recycled into pulp as a basic material for making new sheets of paper. Recycled paper panel can be used as building elements. The objects of observation in this research include the manufacturing process and water resistance of recycled paper panels on a household scale. The process of making paper using a household blender compared with a paper chopper. The resulting paper pulp from these two tools is then mixed, printed, and tested for water resistance. Paper models without binding media were used as standards, compared with organic binding media made from tapioca flour and white adhesives. Four different paper thicknesses were made to test their water resistance performance. As a result, paper with a white adhesive binder can last more than 30 minutes after being exposed to water and when dry can be reused while paper without a binding medium is damaged by water.